2015
DOI: 10.1037/fam0000097
|View full text |Cite
|
Sign up to set email alerts
|

Parent involvement, sibling companionship, and adolescent substance use: A longitudinal, genetically informed design.

Abstract: A large literature shows that parent and sibling relationship factors are associated with an increased likelihood of adolescent substance use. Less is known about the etiology of these associations. Using a genetically-informed sibling design, we examined the prospective associations between parent involvement, sibling companionship, and adolescent substance use at two points in mid- and late-adolescence. Adolescents were adopted (n = 568) or the biological offspring of both parents (n = 412). Cross-lagged pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 55 publications
1
37
0
2
Order By: Relevance
“…It has been well documented that early life experience, including experience with parents, can shape adult cognitive and behavioral functions (Felitti et al, 1998; Repetti et al, 2002; Nishi et al, 2014; Sripada et al, 2014; Jensen et al, 2015; Samek et al, 2015; Yam et al, 2015). In humans, father presence during early development is associated with decreased risk for various psychopathologies and increased well-being of the children (Sarkadi et al, 2008; McLanahan et al, 2013; Tikotzky et al, 2015), whereas father absence can lead to negative outcomes including the development of depressive symptoms and externalizing behaviors (Phares and Compas, 1992; Culpin et al, 2013; McLanahan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that early life experience, including experience with parents, can shape adult cognitive and behavioral functions (Felitti et al, 1998; Repetti et al, 2002; Nishi et al, 2014; Sripada et al, 2014; Jensen et al, 2015; Samek et al, 2015; Yam et al, 2015). In humans, father presence during early development is associated with decreased risk for various psychopathologies and increased well-being of the children (Sarkadi et al, 2008; McLanahan et al, 2013; Tikotzky et al, 2015), whereas father absence can lead to negative outcomes including the development of depressive symptoms and externalizing behaviors (Phares and Compas, 1992; Culpin et al, 2013; McLanahan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in parental environment during development can affect adult phenotype in profound ways (Heim et al, 2002; Repetti et al, 2002; O’Donnell et al, 2014; Samek et al, 2015). In humans, for example, childhood family environments characterized by high conflict and low quality attachments are associated with vulnerability to social and emotional processing deficits (Repetti et al, 2002) as well as an increase in the risk for developing psychopathology in adulthood (Bifulco et al, 1991; Brown and Anderson, 1991; Felitti et al, 1998; Heim et al, 2002; Yam et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, adolescents with strong familial values are less likely to use substances such as cigarettes, alcohol, and marijuana [49]. In addition to family values, parental involvement, sibling companionship, as well as overall low levels of family conflict and high family cohesion, have the potential to buffer adolescents from substance use [5051]. Thus, positive family environments can protect adolescents against the initiation and maintenance of substance use.…”
Section: Neural Correlates Of Family Influence On Risk Taking and Submentioning
confidence: 99%
“…7 More recently, a study has shown that parental involvement in a child’s life during early adolescence reduces the chances of substance use later on in adolescence. 8 …”
Section: Introductionmentioning
confidence: 99%